Current Diagnosis and Treatment Models of Periodic Fever, Aphthous Stomatitis, Pharyngitis and Cervical Lymphadenitis Syndrome - Ayşenur Paç Kısaarslan; Emel Kabakoğlu Ünsür; Betül Sözeri (Galenos Yayinevi, 2017)
Periodic fever, aphthous stomatitis, pharyngitis, and cervical lymphadenitis (PFAPA) syndrome is the most frequent cause of periodic fever in childhood. The pathogenesis of PFAPA is still unknown. Differantial diagnosis must be made with cyclic neutropenia and other autoinflammatory diseases. Because PFAPA is self limiting and benign, there is no certain treatment model. Treatment options must be specific to the patient, with a strong family and doctor relationship.